Griots, satirical columns, and the micro-public sphere. (1st September 2015) - Tomaselli, Keyan; Sakarombe, Phebbie
This reflexive study examines the idea of African storytelling. It sheds light on a specific university newspaper column, The UKZN Griot. A critique of neoliberal managerialism backgrounds the discussion of the satirical column that examines the local in relation to global issues of academic governance. The Habermasian theory of the public sphere frames the discussion. Responses to the column are analysed in terms of power relations, resistance and democracy.